Systemic hormone therapy and dementia: A nested case-control and co-twin control study. (November 2022) - Løkkegaard, Laura Ekstrøm; Thinggaard, Mikael; Nygaard, Marianne; Hallas, Jesper; Osler, Merete; Christensen, Kaare
Highlights: This population-based study controls for important covariates such as education. The study also includes a co-twin control design controlling for familial factors. Dementia risk was associated with hormone therapy initiated before 2003, when it was more common. The findings could be due to confounding by indication as no dose–response relationship was found. The lack of association from 2003 onwards could be due to the comparatively short follow-up. Abstract: Objective: The effect of systemic hormone therapy (HT) on dementia risk is unclear. Our aim was to investigate the association between HT and dementia. Study design: This register-based study consists of a nested case-control study and a co-twin control design, which controls for familial confounding, including shared genetics. Main outcome measures: Through Danish national registries from 1995 to 2011, we identified: a) 2700 female singletons with incident dementia and 13, 492 matched controls; b) 288 female twins with incident dementia and co-twins without dementia. Data on HT and education were retrieved, and analyses were performed using conditional logistic regression and McNemar's χ 2 -test. HT use decreased dramatically after the Women's Health Initiative study results were published in 2002, and the analyses were stratified accordingly to account for potentially different HT user characteristics. Results: The odds ratio (OR) for the association between systemic HT and dementia was 1.05, 95% CI = [0.93–1.19] in singletons and 2.10, 95% CI = [0.99–4.46] in twins. A statistically significant association was found for systemic HT before 2003 in both populations, with an OR of 1.14, 95% CI = [1.01–1.28] in singletons and an OR of 2.20, 95% CI = [1.04–4.65] in twins. Conclusion: Using Danish nationwide registries and controlling for education and for familial factors in a subsample, systemic HT was found to be associated with increased dementia risk if used before 2003, when HT was more commonly prescribed.